Salmonella produces sulfide to compete with Escherichia coli in the gut lumen - Anaïs B. Larabi; Connor R. Tiffany; Hugo L. P. Masson; Henry Nguyen; Eli J. Bejarano; Megan J. Liou; Lauren C. Radlinski; Aurore M. Demars; Renée M. Tsolis; Andreas J. Bäumler (Proceedings of the National Academy of Sciences, 2025)
Hydrogen sulfide production is a characteristic that distinguishes Salmonella serovars from closely related species, such as Escherichia coli , but its biological significance remains obscure. Here, we show that PhsABC and AsrABC-mediated hydrogen sulfide production by Salmonella enterica serovar ( S. ) Typhimurium was linked to an increased abundance of Deltaproteobacteria and inhibition of cytochrome bd oxidase-mediated aerobic respiration of Escherichia coli in the murine large intestine. Functional phsABC and asrABC operons provided a growth benefit to S. Typhimurium in the cecum of Enterobacterales- free conventional mice only upon inoculation with commensal E. coli. In gnotobiotic mice engrafted with a defined community of 17 human Clostridia isolates, S. Typhimurium infection inhibited cytochrome bd oxidase-mediated aerobic respiration in E. coli only in the presence of Desulfovibrio piger , a sulfide-producing representative of the Deltaproteobacteria. A S. Typhimurium strain deficient for hydrogen sulfide production ( phsA asrA mutant) did not inhibit cytochrome bd oxidase-mediated aerobic respiration in E. coli , even when D. piger was present. Collectively, these data suggest that the phsABC and asrABC operons of Salmonella serovars provide a benefit during competition with closely related bacteria, such as E. coli , by inhibiting cytochrome bd oxidase-mediated aerobic respiration of the commensal.